Emotional Reactivity in Adolescents With Non-suicidal Self-injury and Its Predictors: A Longitudinal Study - Kandsperger, Stephanie; Schleicher, Daniel; Ecker, Angelika; Keck, Florentina; Bentheimer, Sebastian; Brunner, Romuald; Jarvers, Irina (Frontiers in Psychiatry, 2022)
Background: The management of emergency presentations at child and adolescent psychiatric outpatient clinics, by children and adolescents with self-injurious thoughts and behaviors, represents very responsible tasks but also offers the opportunity for immediate interventions. The stability and degree of emotional reactivity (ER) is a significant psychopathological symptom for development and maintenance of self-injurious behavior, differentiating between those who have continued to injure themselves and those who have not. In general, the relationship between ER and self-injurious behavior has been shown to be bidirectional. However, the stability of ER over time, as well as important predictors for ER itself have not been investigated so far. Therefore, this present study aimed at investigating the stability of ER over time and the relationship between non-suicidal self-injury (NSSI and ER. Reinforcement functions and several variables of psychological functioning were considered as possible influencing factors. Methods: As part of a longitudinal study, 97 adolescents aged 11 to 18 years who presented due to self-injurious thoughts or behaviors underwent standardized emergency management. This included a specified detailed psychiatric assessment at baseline (including the Emotion Reactivity Scale, ERS, and the Self-Injurious Thoughts and Behaviors Interview, SITBI) and treatment recommendations. These were followed by a catamnestic examination with two follow-up appointments. Changes over time in ER, NSSI, reinforcement functions of NSSI and general indicators of psychological functioning (General Severity Index, GSI) were examined and significant correlations were followed up by a linear-mixed effect model predicting the ERS score over time. Results: Data analysis revealed a statistically significant decrease in ERS scores and GSI over time. However, reinforcement functions for and the symptomatology of NSSI did not change. Furthermore, no predictive relationship from ER to NSSI could be identified. A linear-mixed effect model predicting the ERS identified the GSI, automatic positive reinforcement (as a reinforcement function for NSSI) and age as the only significant predictors. Conclusion: Results demonstrate the importance of NSSI reinforcement functions for heightened emotional reactivity and emphasize their role as a point for therapeutic intervention by providing alternatives to NSSI and thereby possibly reducing emotional reactivity.